Pengaruh Hasil Belajar Matematik Dengan Menggunakan Model Pembelajaran Cooperative Tipe Make A Match Terhadap Siswa SMK - Hindun Jariyah; Anggita Tri Indahsari; Luvy Sylviana Zanthy (Journal on Education, 2019)
In general, mathematics is a very boring and frightening lesson. So students feel unmotivated to lHHearn and a little curiosity, this causes low student learning outcomes in mathematical lessons. For this reason, improvement efforts are needed in the learning process by choosing the appropriate and appropriate learning model to use. The purpose of this study was to improve the mathematics learning outcomes of vocational students using the cooperative learning model type make a match. This research was conducted at TI Garuda Nusantara Vocational School Cimahi as the population, and the sample was X Multimedia 1 class, which amounted to 35 students. Data was collected using observation sheets for teacher activities, student activities, and written tests. Data analysis techniques used in descriptive way using data tables. From the results of the analysis carried out with the cooperative learning model type make a match proved to be able to improve student learning outcomes, especially in the field of Multimedia study in class X at TI Garuda Nusantara Cimahi Vocational School.